Teaching Analytical Instrumental Analysis to Undergraduates in Specialized Degree Programs with Heterogeneous Prior Knowledge: Reflections on Inquiry Based Lecture Activities - Kirsten A. Tucker; Peter L. Pingerelli (Journal of Scholarly Engagement)
An adjunct faculty member and graduate instructional assistant (GIA) introduced inquiry-based activities into a 20-student undergraduate analytical instrumental analysis (AIA) lecture course, and reflect on their teaching assumptions, practices and experiences. The increased need for interdisciplinary scientific programs now has an AIA course serving multiple Bachelor of Science degrees in environmental sciences, forensic sciences, molecular biology, and secondary science education. However, we learned degree specialization also introduces into a course, student populations possessing heterogeneous prior knowledge, making an instructor’s rendering of student prerequisite skills a greater challenge. Guided by a pretest assessment, instructional activities were modified or developed by the authors and aimed at enhancing student engagement and motivation to mitigate prior knowledge gaps, improve analytical problem-solving skills, and facilitate a deeper understanding of modern instrumentation design and function. Detailed activity rationale and descriptions are presented. Activities included using readily available Internet bioinformatics and database tools for analytical problem-solving; demonstrating principles of electronic hardware and software design and integration; and creating interdisciplinary scientific narratives using biological, environmental, and industrial molecular exemplars. Our teaching reflections reference weekly post-lecture instructor/GIA discussions, strategic student questioning, collaborative classroom activity observations, and formative assessments. We propose continual instructional reflection is essential for a course serving multiple specialized degrees programs in a scientific field and facilitates preparation for students entering the workforce or graduate school. Further, our observations suggest inquiry-based, real-world activities relevant to modern instrumentation and its applications, assisted students in resolving heterogeneous prior knowledge gaps.